The effect of marketing mix and after sales service toward brand equity - Roya bakhshinezhad shamami; Bahram Kheiry (Journal of Economics, Business, and Accountancy Ventura, 2019)
The present research aimed to study the effect of the marketing mix (price, product, place, promotion) and after-sales services on three dimensions of brand equity (perceived quality, brand loyalty, and brand awareness) using the Aaker Model. After-sales service in the automotive industry is emphasized as a key and effective element in the promotion of perceived quality, brand loyalty, brand equity, and even products pricing. It is a descriptive survey in which the required data were collected using a questionnaire. The statistical population included the buyers of products of Iran Khodro Diesel Company who have used the sales and after-sales services of this company, 384 of whom were selected as the sample. The obtained data were analyzed using Smart PLS-2 and SPSS-21. The results indicated that product; place (distribution), promotion (advertisement), and after-sales services have a significant impact on dimensions of brand equity.